MODELLING OF THE EFFECTS OF THE ENVIRONMENTAL-GEOPHYSICAL STATE OF SOILS ON ENGINEERING BUILDING OBJECTS - Starodub, Yu.; Havrys, A.; Kozionova, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article deals with the method of the reaction modelling of soil strata under engineering objects to ecological and geophysical state in the problems of studying the negative influence of loads on a stress-strain state of soil under engineering objects. The problem of stability study is considered and the behaviour of soil in a vicinity of bridge-engineering structures is investigated. To solve the problems of emergency protection, a method of modelling the reaction of the soil layer under the load on the engineering objects due to tectonic influences to study the stress-strain state of the ground crust in a vicinity of engineering objectsis used. An algorithm of the finite element method in the problem of studying the stress-strain state of soil base under engineering objects has been developed. The physical and mathematical formulation of the problem is carried out. The modelling problem is solved by test cases. Models of continuous environment of functioning engineering structures for which stress-strain characteristics of the soil massif modelled are developed. The theoretical definition and modelling of critical values of the stress-strain state of the soil mass under the influence of loads are carried out. Modelling allows to predict the nature of the influence of mechanical processes on the ecological and geophysical state of the environment and to study the stability of engineering structures. Stress-deformation processes of the rock massif are investigated, as a result of which emergencies of natural and man-made characters can arise.
Keywords: soil; ecological and geophysical state; loaded engineering objects